Scaling sustainable livestock technologies: harnessing data for climate resilience and mitigation in Colombia - Arango, Jacobo; Matiz, Natalia; Cardoso, Juan Andres; Burkart, Stefan; Idupulapati, Rao; Costa, Ciniro Jr.; Marin, Alejandra; Pérez, Juliana (2024)
In Colombia, ranchers are adopting innovative practices to address climate change and improve livestock productivity. Central to this transformation is a geospatial database (GDB) developed within the Livestock and Climate initiative, which provides comprehensive data on sustainable livestock practices implemented across 377 farms in Colombia's Caquetá region.